Proceedings of the 59th Annual Meeting of the Association for Computational Linguistics and the 11th International Joint Confer 2021
DOI: 10.18653/v1/2021.acl-short.42
|View full text |Cite
|
Sign up to set email alerts
|

Zero-shot Event Extraction via Transfer Learning: Challenges and Insights

Abstract: Event extraction has long been a challenging task, addressed mostly with supervised methods that require expensive annotation and are not extensible to new event ontologies. In this work, we explore the possibility of zeroshot event extraction by formulating it as a set of Textual Entailment (TE) and/or Question Answering (QA) queries (e.g. "A city was attacked" entails "There is an attack"), exploiting pretrained TE/QA models for direct transfer. On ACE-2005 and ERE, our system achieves acceptable results, ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…For RE, Wang et al (2021a) propose a text-to-triple translation method that given a text and a set of entities returns the existing relations. For EE, Lyu et al (2021) to us, the use of an entailment model, but in their case the input sentence is split in clauses according to the output of a Semantic Role Labelling system. In order to compare their results with ours, we only use the event types, not the trigger information 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For RE, Wang et al (2021a) propose a text-to-triple translation method that given a text and a set of entities returns the existing relations. For EE, Lyu et al (2021) to us, the use of an entailment model, but in their case the input sentence is split in clauses according to the output of a Semantic Role Labelling system. In order to compare their results with ours, we only use the event types, not the trigger information 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Similar to TE, (Clark et al, 2019) performs yes/no Question Answering, in which a model is asked about the veracity of some fact given a passage. Lyu et al (2021) recast the zero-shot event extraction as a TE task, using TE model to check whether a piece of text is about a type of event.…”
Section: Related Workmentioning
confidence: 99%
“…also experimented in a zero-shot setting where no task-specific data is used for training, only using prompts for probing. The zeroshot setting for the full event extraction pipeline has been explored in Lyu et al (2021) where QAbased prompts are used for argument extraction and prompts based on Textual Entailment (Dagan et al, 2013) are used for trigger classification (see Section 3.3.1 below). Several ablation experiments analyzed the different components of the system such as the choice of PLM, the choice of QA dataset and the way to generate the questions (fixed vs. contextualized).…”
Section: Question Answering As Proxy Taskmentioning
confidence: 99%
“…Some of the works introduce contextualization, integrating relevant words from the text into the question. For example, in argument extraction, the question can include the trigger extracted from the text (e.g Lyu et al, 2021) or another argument that was previously identified (see the Event Extraction row in Table 4). Neural based question generation models can also improve the quality of the question, as in , where monolingual unsupervised machine translation is used to generate the part of the question that does not depend on the template, translating a descriptive statement into a question-style expression.…”
Section: Question Answering As Proxy Taskmentioning
confidence: 99%
“…Event detection (Grishman, 1997;Chinchor and Marsh, 1998;Ahn, 2006) is the task of identifying and typing event mentions from natural language text. Supervised approaches, especially deep neural networks Du and Cardie, 2020;Lin et al, 2020;Lyu et al, 2021), have shown remarkable performance under a critical prerequisite of a large amount of manual annotations. However, they cannot be effectively generalized to new languages, domains or types, especially when the annotations are not enough Lai et al, 2020b;Shen et al, 2021) or there is no annotations available (Lyu et al, 2021;Zhang et al, 2021b;Pasupat and Liang, 2014).…”
Section: Introductionmentioning
confidence: 99%